Спостереження Сонячного затемнення 22 липня 1990 року - Благодир, Я.; Ковальчук, М.; Гірняк, М.; Лаба, І. (Праці наукового товариства ім. Шевченка, 2011)
Scientists of Astronomic Observatory at the Lviv Ivan Franko National University observed a full solar eclipse on July 22nd 1990 at the most conve